THE ABILITY OF TREMBESI TREE (Samanea Saman), JABON (Neolamarckia Cadamba), AND ACASIA (Acacia Mangium) in Absorbing Dust in BENDOSARI PARK, SALATIGA CITY - Pratama, Dimas Karunia; Sutrisno, Alfred Jansen (Universitas Boyolali, 2022)
Air pollution causes serious problems to the environment that will have an impact on living things. Trees are useful as a reduction in pollution caused by the density of vehicle mobility. Dust is one source of pollution from the dense mobility of vehicles. The purpose of this study was to determine the absorption of dust on trees. The research method used was purposive sampling, where Trembesi (Samanea Saman), Jabon (Neolamarckia Cadamba), and Acacia (Acacia Mangium) trees were used as samples. The result of dust absorption. Trembesi Tree (Samanea Saman) is 0.443 mg/cm2 - 0.649 mg/cm2 , Jabon Tree (Neolamarckia Cadamba) is 0.059 mg/cm2 - 0.072 mg/cm2 , Acacia Tree (Acacia Mangium) is 0.127 mg/cm2 - 0.130 mg/cm2 .